A video-based time-motion analysis of an elite male basketball team during a season: game demands according to player position, game quarter, and actual time played - Gervasi, M.; Mennelli, G.; Patti, A.; Sisti, D.; Venerandi, R.; Benelli, P.; Pena, E. F. (International Journal of Performance Analysis in Sport, 2024)
To investigate differences in the game demands of top-level professional basketball players based on their position and the quarter of the game. Thirteen elite male players were assessed on their positions (point guard, guard, forward, and centre) over different quarters (Q1-Q4) during 15 home games. A multivariate analysis of variance was performed using role and quarters as predictors to assess distances, speeds, and accelerations. The guard and point guard covered more distance than the centre and forwards (p > 0.001). The average distance covered was higher (p < 0.01) in Q4 than in the other quarters. Both speed and the percentage of time spent in the jogging to max speed range decreased significantly from Q1 to Q4, while time spent standing and walking tended to increase from Q1 to Q4. The point guard spent the highest percentage of total time performing major accelerations followed by the guard, while the forwards and centre spent less time performing accelerations. Overall, 22.8 ± 0.7% of total playing time was spent performing major accelerations, which decreased from Q1 to Q4. These findings suggest that the positions of elite basketball players vary in terms of the activities demands they place on players, underscoring the need for individualised role-based conditioning.